Makna Takut akan Tuhan Menurut Amsal 8:13 (Studi Evaluasi di Jemaat GPdI “Filadelfia” Oepaleo Kupang) - Nelly Nelly; Rodi Imenuel Nome (Institut Agama Kristen Negeri Toraja, 2020)
Abstract: Fear of God are hates evil; hates pride, hates conceit, hates evil conduct, and hates guile-filled mouths. In the fear of God is also a sign of the quality and morality of a person who can be accountable for his life before God and shows a view of life that contains human proper attitudes that are always shown in everyday life because of his good and close relationship with God. The purpose of this study was to describe the meaning of fearing God according to Proverbs 8:13 in the GPdI